2019
DOI: 10.1017/s0950268818003333
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of rabies virus strain with N-gene that clustered with China lineage 2 co-circulating with Africa lineages in Monrovia, Liberia: first reported case in Africa

Abstract: Despite a long history of dog-transmitted human rabies outbreaks in Liberia, West Africa, no reports exist of molecular characterisation of the causative lyssaviruses. This study investigated Rabies lyssavirus (RABV) strains isolated at the dog–human interface in Monrovia, Liberia 2016 and 2017, by reverse transcription polymerase chain reaction, using primers specific for the nucleoprotein (N) gene. Out of 20 specimens (19 dog brain samples and one human saliva) tested as suspected rabies cases, three (15%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…In their letter, Zhao and colleagues similarly observed that apart from the two RABV strains of China lineage 2 (KU963489 and DQ666322), MF765758 also has very close resemblance (99% similarity) to other RABVs such as the France RABV strain, CVS (GU992321), the India RABV strains, RAB5 and RAB7 (KF535200 and KF535201), and that phylogenetic analysis 'revealed them to be the same lineage'. This statement corroborates our ealier conclusion that phylogenetic evidence suggests that, 'the Monrovia RABV isolate (MF765758) has its origin in Asia, rather than it being an autochthonous (Liberian) RABV or an extant strain from another African country' [4]. In addition, we designated as cosmopolitan, the group of RABVs from across the world that have the same progenitor as MF765758 ( Fig.…”
Section: Sirsupporting
confidence: 85%
See 1 more Smart Citation
“…In their letter, Zhao and colleagues similarly observed that apart from the two RABV strains of China lineage 2 (KU963489 and DQ666322), MF765758 also has very close resemblance (99% similarity) to other RABVs such as the France RABV strain, CVS (GU992321), the India RABV strains, RAB5 and RAB7 (KF535200 and KF535201), and that phylogenetic analysis 'revealed them to be the same lineage'. This statement corroborates our ealier conclusion that phylogenetic evidence suggests that, 'the Monrovia RABV isolate (MF765758) has its origin in Asia, rather than it being an autochthonous (Liberian) RABV or an extant strain from another African country' [4]. In addition, we designated as cosmopolitan, the group of RABVs from across the world that have the same progenitor as MF765758 ( Fig.…”
Section: Sirsupporting
confidence: 85%
“…In addition, we designated as cosmopolitan, the group of RABVs from across the world that have the same progenitor as MF765758 ( Fig. 1) [4]. Previously, Vellasco Villa and others had similarly described a cosmopolitan group of RABV lineages comprising dog-maintained and dog-derived strains belonging to Africa 1 and 4, North America, South America, Europe, Middle East and vaccine lineages [5].…”
Section: Sirmentioning
confidence: 99%
“…However, further analyses showed that the rabies lyssavirus belonging to African lineage 1b, initially thought to be exclusively found in eastern, central, and southern Africa, now occurs in West Africa [13], highlighting the complexity of rabies epidemiology in the region. Furthermore, a rabies lyssavirus strain in Liberia was found to cluster with other rabies viruses in the China lineage 2, confirming transcontinental transmission of the disease [20].…”
Section: Introductionmentioning
confidence: 80%
“…This observation is not limited to Nigeria, as a RABV from Benin (U22485) clustered with one RABV from Cameroon (U22635); also Ghana RABVs (HM368162 and HM368096) clustered with Moroccan RABV (AY062090). Recently, a molecular study of rabies in Liberia demonstrated that rabies lyssaviruses from this country clustered with China lineage-2, indicating transcontinental transmission of rabies [20].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mass vaccination campaigns of dogs have to take into account risks of possible reintroduction of the virus from areas not yet covered by vaccination campaigns, and phylogenetic studies can help assess this risk as shown by Bourhy et al [40], together with FP helping extend availability of samples from remote areas. Using FP or FTA cards can facilitate launching surveillance activities even in difficult contexts as shown in Liberia where, because of the absence of trained personnel, laboratory facilities and cold storage facilities in Liberia at the time, active rabies surveillance relying on the use of FTA cards to collect and preserve samples for subsequent molecular analysis was set up [41]. Unfortunately, activities were suspended shortly after the 2014 Ebola virus outbreak.…”
Section: Discussionmentioning
confidence: 99%